Bisnis Online di Era Revolusi Industri 4.0 (Tinjauan Fiqih Muamalah) - Efrita Norman; Idha Aisyah (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2019)
Online buying and selling has become a preferred shopping alternative to the current 4.0 industrial revolution. However, the existence of online buying and selling is faced with various problems such as goods mismatches, defects in goods, and fraud, making enthusiasts enthusiastic to give an idea about sharia online buying and selling according to Islamic law based on a study of the views of online business people in the Bogor Pamijahan District community. Online buying and selling transactions can be via ATM or COD (Cash On Delivery). The most important thing in buying and selling online is the seller's credibility, quality, price of goods and transaction security. Sharia online buying and selling must also be taken into account so that the seller and buyer of the same fellow Muslims are not harmed and they are happy with each other nor it does violate the fiqh law muamalah in Islam. Islamic Law of Jurisprudence packs online buying and selling in sharia that is fulfilling harmony and terms of sale and purchase, agreement, ethics and principle of buying and selling. The specifications of the goods being traded must be clear and honestly described even if there is a defect in the goods to avoid garar. If the specifications of the item desired by the buyer are not even suitable, the online seller can confirm to the buyer to choose another specification or even cancel the transaction by transferring the payment to avoid fraud and increase customer satisfaction.